Grappling with the Suicidal Monster: - Erica Delaney; Evelyn Gordon (Grounded Theory Review: An International Journal)
Suicidal behaviour is a significant public health concern given the strong association between acts of self-injury and death by suicide—particularly among young people where rates of self-injury are steadily increasing (National Suicide Research Foundation, 2017). Furthermore, carers including parents, relatives, and significant others are being allocated increasing responsibility in assisting mental health care services in the early detection and management of family members at risk of suicide (Chiang, Lu, Lin, Lin, & Sun, 2015). Thus, it is essential to understand how this vital role is experienced by parents in order to ensure that sufficient supports are made available to them. However, there is a paucity of literature relating to this phenomenon. This grounded theory (Glaser & Strauss, 1967) study generated a substantive theory about how parents experience living with young adults who are in suicidal distress.